Pancreatic L-Glutamine Administration Protects Pig Islets from Cold Ischemic Injury and Increases Resistance toward Inflammatory Mediators. Issue 3 (March 2016) - Brandhorst, Heide; Theisinger, Bastian; Guenther, Bernhard; Johnson, Paul R.; Brandhorst, Daniel
The isolation and transplantation of porcine islets represent a future option for the treatment of type 1 diabetic patients. Stringent product release criteria and limited availability of transgenic and specific pathogen-free pigs will essentially require processing of explanted pig pancreata in specialized, possibly remote isolation facilities, whereby pancreata are exposed to cold ischemia due to prolonged tissue transit time. In the present study we investigated whether pancreas oxygenation can be efficiently combined with an antioxidant strategy utilizing intraductal L-glutamine administration. Pig pancreata were intraductally perfused after retrieval and after cold storage in oxygen-precharged perfluorohexyloctane utilizing University of Wisconsin solution supplemented with ( n = 16) or without ( n = 14) 5 mmol/L L-glutamine. After isolation purified islets were subjected to extensive quality assessment. Islet recovery postpurification was significantly higher in glutamine-treated pancreata (77.0 ± 3.3% vs. 60.3 ± 6.0%, p < 0.05). Glutamine administration increased intraislet content of reduced glutathione (117.8 ± 16.5 vs. 15.9 ± 2.8 ng/ng protein, p < 0.001) associated with increased islet recovery after culture (65.8 ± 12.1% vs. 40.3 ± 11.7%, p < 0.05), enhanced glucose stimulation index (1.82 ± 0.16 vs. 1.38 ± 0.10, p < 0.05), and improved posttransplant function in diabetic nude mice ( p < 0.05). Furthermore, intraductally administered glutamine increased pig islet resistance toward reactive oxygen species, nitric oxide, and high-dose proinflammatory cytokines. The present study demonstrates that quality and function of pig islets exposed to warm and cold ischemia can significantly be improved using intraductal L-glutamine administration. As the efficiency of the intraductal route may be inferior compared to intravascular administration further studies should aim on assessment of L-glutamine as supplement for pancreas perfusion during organ procurement.